O sistema Toyota de produção e teoria das restrições como base para análise da função produção em empresas do setor têxtil: proposição de um instrumento de diagnóstico - Silva, Núbia Adriane da (Universidade do Vale do Rio dos Sinos, 2016)
Owing to globalization and the consequent increase in competition between companies and countries, companies need to seek, among a wide range of alternatives, develop management methods that enhance their competitiveness by valuing attributes linked to the Production System. The principles, methods and techniques related to improvement in production systems have had greater application visibility and in large industrial companies. In this general context, it is dealing with textile companies representing a market segment growing, little studied in relation to the use of modern methods and techniques of production management. This study presents a proposal for an instrument to map the improvement points of the Production Function (Function Process and Function Operation) in micro and small industrial enterprises from the principles of the Toyota Production System (TPS) and the Theory of Constraints (TOC). The idea is to make it clear that significant improvements in the production system are likely to assist in improving the organizational environment and the competitiveness of enterprises. This research used as a methodological basis the Design Science Research. The basis for the development of the method were: a) construction of the theoretical framework; b) preparation of the questionnaire; c) pre-test and re-adaptation of the questionnaire; d) field work (data collection in the field); e) critical description of cases; and f) instrument proposition. The development and evaluation of the instrument were performed in textile companies located in Paraíso do Tocantins, in the state of Tocantins. This way, it presents a focused instrument to diagnose and verify the improvement potential of micro and small companies in the textile sector facing the Production Function. With its application, it is possible to check the suitability of using it, opposite the organizational environment, facilitating the manager to propose targeted improvements, aimed at remedying the problems encountered, increase production and profitability.
Keywords: Avaliação de desempenho; Função produção; Pequenas empresas; Sistema Toyota de produção; Teoria das restrições; Performance evaluation; Production function; Small business; Toyota production system; Theory of constraints; ACCNPQ::Engenharias::Engenharia de Produção